Acute right lower limb deep venous thrombosis due to pressure from large adenomyotic uterus-laparoscopic management - Anagani, Manjula; Agrawal, Prabha; Agrawal, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A 48-year lady came with abnormal uterine bleeding with 22 weeks size adenomyotic uterus compressing on right common iliac, external iliac and femoral vein leading to acute deep venous thrombosis (DVT). She had history of severe anaemia secondary to menorrhagia with multiple blood transfusions and medical management with tranexamic acid and oral and intrauterine progesterone for 2 years. She presented with right leg swelling and discoloration for 1 day, and a doppler ultrasound confirmed an extensive DVT. Limb saving procedure was taken up immediately with right femoral vein catheterization and venoplasty followed by heparin infusion and thrombolysis for total 48 hours. After 12 hours of stopping heparin drip total laparoscopic hysterectomy was done in view of continuous bleeding and to decrease pressure on iliac vessels. Post-operative heparin infusion started in 8 hours and patient was discharged in stable condition 48 hours post-surgery. Histopathological examination confirmed adenomyosis with weight of specimen being 1.5 kg. Large uterine fibroids are a well-known cause of DVT and/or pulmonary embolism (PE). However, reports of large uterine adenomyosis causing DVT secondary to pelvic compression are scanty.